Community Service-Learning: Why Can’t Canada Be More Like Mexico? (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
In Mexico, the community service strategy and requirements for undergraduate students are both longstanding and mandated by the Mexican Constitution. Students undertake a minimum of 480 hours of service during their undergraduate degrees, which are coordinated through their universities’ Social Service (SS) departments. Many Canadian universities and colleges offer community service through courses and volunteer programs; however, the practice and adoption levels vary widely. Student involvement with community partners, as represented through community service-learning (CSL) and volunteerism in Canada, are sponsored by many post-secondary institutions but are not driven by a national agenda. While, in Mexico, community service is documented at a departmental and institutional level for reporting to stakeholders and the government, in Canada, documentation of community service varies with the institutional mandate and is often sporadic or non-existent; the imperative for systematic student engagement and citizenship development has not been recognized at the national level. This research paper provides an overview of the community engagement practices in both countries, with the national patterns represented through a summative review of selected Canadian and Mexican universities. Suggestions for processes and practices for Canada are proposed based upon the Mexican model.